The pocket guide to the DSM-5-TR diagnostic exam - Nussbaum, Abraham M., 1975-; American Psychiatric Association Publishing (Washington, DC : American Psychiatric Association Publishing, 2022)
'Designed for interviewers at all levels of experience, The Pocket Guide to the DSM-5-TR Diagnostic Exam is the clinician's companion for using DSM-5-TR in diagnostic interviews. Beginning with an introduction to the diagnostic interview, the Pocket Guide addresses the goals of the interview, provides an efficient structure for learning how to conduct one, reviews the screening questions, and then explains the ways in which DSM-5-TR, with its updated approaches to diagnosis and classification, impacts the interview. The core of the guide walks the reader through a complete diagnostic exam that includes the follow-up questions for each class of DSM-5-TR disorders. The book is useful for beginners learning the format and flow of the diagnostic interview and for seasoned clinicians conducting an interview consistent with the DSM-5-TR. The Pocket Guide to the DSM-5-TR Diagnostic Exam is a pragmatic and concise resource for diagnosing a person in mental distress while establishing a therapeutic relationship'--
Introduction to the Diagnostic Interview -- Alliance Building During a Diagnostic Interview -- The 30-Minute Diagnostic Interview -- Personalizing Diagnoses Through Dimensions -- Key Changes in DSM-5-TR -- The DSM-5-TR Diagnostic Interview -- A Brief Version of DSM-5-TR -- Six Questions to a Differential Diagnosis -- A Mental Status Examination : With Essential Psychiatric Glossary -- Mental Health Treatment Planning -- The American Board of Psychiatry and Neurology Clinical Skills Evaluation -- Selected DSM-5-TR Assessment Measures -- Dimensional Diagnosis of Personality Disorders -- Alternative Diagnostic Systems and Rating Scales.
REFER RECORD NO. b16932432
Includes bibliographical references and index.
Keywords: Diagnostic and statistical manual of mental disorders; Mental Disorders -- diagnosis; Interview, Psychological -- methods; Physician-Patient Relations; Handbook